PENGEMBANGAN MEDIA PEMBELAJARAN WEBSITE BERBASISGOOGLE SITES PADA MUATAN IPS MATERI INDAHNYA KERAGAMAN BUDAYA NEGERIKU SISWA KELAS IV SDN 68/VIII DESA TERITI KABUPATEN TEBO - ., Amril; Saputra, Riyadi; Azra, Wilda Sari Fitri (Jurnal Tunas Pendidikan, 2024)
In IPS learning there is plant breeding material. Regarding the material during the learning process, the teacher still lacks useful media to make it easier for students to understand abstract material. So in this study developed a website learning media based on google sites on social studies learning to overcome this problem. The purpose of this research is to develop learning media for websites based on Google Sites for social studies learning, as well as to produce valid, practical and effective media. The type of research used in this research is research and development (R&D). This development procedure refers to the development of the ADDIE model which consists of several stages, namely (1) Analysis Phase, (2) Design Stage, (3) Development Stage, after going through the development stage a validation test is carried out by 3 validators with 80% results (4) Implementation Stage, at this stage practicality tests were carried out by practitioners (teachers) and (students) with 82% results after that a video media trial was carried out with an effectiveness sheet to get 76% results by obtaining student learning outcomes, (5) Evaluation Stage (Evaluation). Based on the ADDIE procedure used in the research above, it can be concluded that the google sites-based website learning media that has been developed by researchers is feasible to use, because it meets the minimum valid, practical and effective criteria.